2016
DOI: 10.1016/j.heares.2016.08.006
|View full text |Cite
|
Sign up to set email alerts
|

Modelling the effect of round window stiffness on residual hearing after cochlear implantation

Abstract: Preservation of residual hearing after cochlear implantation is now considered an important goal of surgery. However, studies indicate an average post-operative hearing loss of around 20 dB at low frequencies. One factor which may contribute to post-operative hearing loss, but which has received little attention in the literature to date, is the increased stiffness of the round window, due to the physical presence of the cochlear implant, and to its subsequent thickening or to bone growth around it. A finite e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
34
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(36 citation statements)
references
References 48 publications
2
34
0
Order By: Relevance
“…Also, it can be noted that the effect of OW and RW stiffness increase has a greater effect in the SSCD condition ( Figure 8B ) compared to the healthy ear. The predicted loss from the RW stiffness increase in Figure 8A is similar to that estimated in Elliott et al ( 41 ), using a similar type of model.…”
Section: Discussionsupporting
confidence: 86%
See 1 more Smart Citation
“…Also, it can be noted that the effect of OW and RW stiffness increase has a greater effect in the SSCD condition ( Figure 8B ) compared to the healthy ear. The predicted loss from the RW stiffness increase in Figure 8A is similar to that estimated in Elliott et al ( 41 ), using a similar type of model.…”
Section: Discussionsupporting
confidence: 86%
“…This means that other AC pathways that may become important when the ossicular chain transmission is restricted is omitted in the current model. The model is similar to other lumped-element models of the inner ear where the stimulation is by AC ( 31 , 40 , 41 ). Moreover, the model could predict intra-cochlear sound pressures obtained experimentally in cadaveric temporal bones when the stimulation was a sound pressure in the ear canal ( Figures 3A,B ).…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, occlusion of the round window is thought to induce a hearing loss (108, 109). In the series by Silverstein et al, hearing loss was the only subjective survey measure that did not improve after round window reinforcement (106), others have reported a conductive hearing loss (105), and additional series of patients undergoing round window reinforcement by some of the authors have shown a mild hearing loss with this surgery in the non-dehiscent ear (110, 111).…”
Section: Treatmentmentioning
confidence: 99%
“…The components used to model Z Diff (Fig. 6A) are the same as Elliott et al 2016 and has a parallel orientation as similar to the model of Lynch et al 1982. The model resistance accounts for the distributed partition and scala impedance (Zwislocki, 1963), while the parallel inductor can be attributed to the helicotrema (Dallos, 1970).…”
Section: Discussionmentioning
confidence: 99%
“…Measurements of intracochlear sound pressures and ossicular motions quantify important mechano-acoustic properties of the ear. Knowledge of the impedances of the middle and inner ear are necessary to understand the intricacies of sound transmission through the inner ear (Elliott et al, 2016; Nakajima et al, 2009; Stieger et al, 2013). Our pressure measurement techniques combined with velocity measurements of the stapes and round window are valuable in determining the sound transmission mechanisms that dominate during various forms of inner-ear stimulation (e.g.…”
Section: Introductionmentioning
confidence: 99%